Examining the impact of covid on the psychosocial profile and academic performance of university students. A pre-post study - Gavín-Chocano, Óscar; García Martínez, Inmaculada (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objective of this study was to evaluate emotional intelligence and life satisfaction in 69 Social Education students. The results showed higher scores in the variables of emotional intelligence and life satisfaction in the posttest evaluation when comparing the values of the medians (Mdn pre vs Mdn post), with lower academic performance (Mdnpost=8.00 < Mdnpre=6.90). In relation to gender in the pretest measure, rank differences were obtained only in the factor evaluating one's own emotions, with the effect size Hedges'g equal to .5996. The practical consequences will allow us to reflect on the effects caused by the pandemic in the university context.